BIOCHEMICAL SUBSTANTIATION OF COMBINED THERAPY APPLICATION IN THE ACUTE PHASE OF EXPERIMENTAL HELMINTHIASIS OF ANIMALS - E. A. Grishina; A. A. Erovichenkov (Журнал инфектологии)
The purpose of this study was to investigate the influence of the invasion process and different strategies of treatment on some biochemical blood indices of mice infested with Syphacia obvelata and Trichocephalus muris of gastrointestinal tract, in order to optimize etiotropic therapy and improve its efficiency. Materials and methods. In the experiment were used albino mice, divided into the following groups: intact animals (control group); animals infected with Syphacia obvelata; animals infected with Trichocephalus muris; infected animals, who received a single dose of albendazole (7 mg/kg); infected animals, who received a single dose of albendazole (7 mg/kg) and gamavit dose intramuscularly (0.3 cm3/kg) simultaneously. Blood for the studies was taken from the animals at 1, 3, 7, 10, 14, 17, 21 days after the infection and after drug administration. From biochemical parameters were determined activities of next enzymes: alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transferase (γ-GTP) and alkaline phosphatase (AP) – with kinetic method IFCC. Results. Infecting animals with helminthes caused a noticeable increase in AP and gamma-GTP levels and cytolytic activity of enzymes: ALT and AST compared with intact group. The above-mentioned complex of metabolic changes clearly reveals a disturbance in hepatocyte metabolism that leads to the decrease in detoxifying function of the liver. This can be apparently explained with toxic effects of helminthes waste products. Albendazole mono-therapy in the therapeutic dose (7 mg/kg) of mice infected with both Syphacia and Trichocephalus caused an even greater increase in ALT and AST levels and also increased serum levels of alkaline phosphatase and γ-GTP, compared with the control and infected animals, that clearly shows an additional toxic effect from the antihelmintic drug. The use of albendazole in combination with a complex antioxidant “Gamavit” in animals infected with both Syphacia and Trichocephalus caused a gradual decrease in serum concentrations of alkaline phosphatase and γ-GTP, and a reduction in ALT and AST levels almost to control values. As a result of this treatment were normalized processes of protein synthesis, antitoxic liver function returned to normal levels and were decreased levels of endogenous intoxication. Conclusion. Thereby, in consideration of this dynamics of blood beochimical parameters in we can conclude that the animal invasion provokes hepatotoxic effect in the host organism, which is further enhanced with the albendazole etiotropic mono-therapy. At the same time integrated antihelminthic therapy with simultaneous application of antioxidant drug “Gamavit” and albendazole stimulates cell energy metabolism, detoxification and hepatoprotective effect. Consequently, the use of complex antihelminthic therapy in combination with antidote therapy in pathologies of parasitic origin is highly relevant and appropriate.